WANPRESTASI IN THE CONSTRUCTION SERVICE AGREEMENT IN THE GENERAL WORKING AND SPATIAL SERVICE - Sri Mustikasari M.Saleh; Abdul Qahar; Zainuddin (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal